Kebijakan Pendidikan Berbasis Keunggulan Daerah - Rino, Rino (Fakultas Ilmu Sosial Universitas Negeri Padang, 2011)
ABSTRACT Educational policy undertaken by centralized proven so far was unable to represent all differences and needs of each region in Indonesia which has a diversity of both natural and resource potential of the strategy development. The decentralization of educational policy with optimize potential of the region through the mechanism of the regional autonomy was considered quite effective to build self-reliance, the creation of high participation of society in the education process Kata Kunci: Kebijakan pendidikan, keunggulan daerah, potensi daerah, desentralisasi